KONVERSI LIMBAH CAIR TAHU MENJADI GAS BIO MENGGUNAKAN AKTIVATOREFEKTIF MIKROORGANISME 4 (EM4) - Ismiyati, Ismiyati (Konversi, 2012)
ABSTRACT. Tofu liquid waste has a high potential to pollute water ecosystem, because so far it is disposed as is to sewerages around tofu factories. Nevertheless, tofu liquid waste is potentially convertible into biogas because it has BOD and COD exceeding 4000 mg/lt.The production of biogasfrom tofu liquid waste using an activator Effective Microorganism (EM4) is influenced by several underlying factors: volumes of waste,goat rumen and EM4. The objective of this study is to understand the feasibility of tofu liquid waste as a raw material of biogas, using additional materials of goat rumen and EM4 activator. The experiments were carried out in 5 batch reactors filled with 3000 ml waste and 300 ml rumen, and added with EM4activator varied for 0 ml, 25 ml, 50 ml, 75 ml and 100 ml. Based on our observations, it can be concluded that the addition of EM4in a batch process is positively correlated to the organicdecay of tofu liquid waste into biogas. The best result was observed in Reactor IV containing 75mlEM4where the biogas was produced after 72 hours. Keywords: tofu liquid waste, EM4 activator, cattle rumen, biogas